MIMO System Capacity based on Multiple fading channels and varying numbers of antennas including the comparison of MIMO-NOMA and MIMO-OMA - Islam, Md. Shariful; Mahmud, Md Ashek Raihan; Jewel, Md Khalid Hossain (IAES Indonesian Section, 2023)
Multiput-Input, Multiple-Output (MIMO) systems have greatly improved data speed, connection stability, and spectrum efficiency, revolutionizing wireless communication. In cases where numerous fading channels coexist and the number of antennas at both the transmitter and receiver fluctuates, this paper examined the functionality of MIMO systems. In actual wireless settings, fading channels frequently occur, resulting in time-varying and spatially correlated channel characteristics. In this paper, we used a thorough analysis to investigate the capability of MIMO systems under some difficult circumstances. We considered circumstances with various numbers of antennas, channel correlation, and fading statistics, ranging from Single-Input, Single-Output (SISO) to MIMO setups. We investigated the impact of geographic diversity, Rayleigh, Rician, Nakagami fading models, and correlated fading channels on system performance. The trade-offs between the quantity of antennas, channel correlation, and capacity in MIMO systems are well illustrated by our findings. We presented our evidence in this paper to show that MIMO-NOMA is solely superior to MIMO-OMA in terms of total channel capacity, except in scenarios where communication is limited to one individual, with a power disparity for which MIMO-NOMA can achieve strictly larger rate pairs than MIMO-OMA. This study also explored the outage probability (OP) performance of MIMO-NOMA and MIMO-OMA systems in a massive MIMO communication scenario, including different fading channels. Based on these findings, we demonstrated that MIMO-NOMA can achieve a higher total ergodic capacity than MIMO-OMA.